Collaboratively Designing a National, Mandated Teaching Performance Assessment in a Multi-University Consortium: Leadership, Dispositions and Tensions - Mcgraw, Amanda; Keamy, Ron; Kriewaldt, Jeana; Brandenburg, Robyn; Walker, Rebecca; Crane, Nadine (Edith Cowan University, 2021)
It is a requirement for pre-service students in Initial Teacher Education programs in Australia to successfully complete a teaching performance assessment (TPA) before they graduate. This follows similar requirements in other international contexts, particularly the United States, where standard-based assessment is also a focus. As members of the design team of a TPA, which was affirmed by a nationally appointed Expert Advisory Group in Australia, we examine the social processes contributing to the development of a high-stakes assessment task. Significant challenges emerged through the nature of the task and the responsibility developers had for ensuring validity and fairness, but also because the design team comprised of teacher educators from ten universities. Using collaborative self-study as a methodology we examine our reflexive narratives and find that collaborative leadership and key personal dispositions are at the heart of the design process. These enable us to identify, examine and navigate arising tensions.